A novel xylene-free deparaffinization method for the extraction of proteins from human derived formalin-fixed paraffin embedded (FFPE) archival tissue blocks - Mansour, Anthony (2014)
Protein detection methods in formalin-fixed paraffin embedded (FFPE) tissue blocks are widely used in research and clinical setting in order to diagnose or to confirm a diagnosis of various types of diseases. Therefore, multiple protein extraction methods from FFPE tissue sections have been developed in this regard. However, the yield and the quality of proteins extracted from FFPE tissues are significantly reduced in blocks stored for longer periods of time. Regardless the protein extraction method used, tissue sections must be first deparaffinized with xylene, and then washed in serial dilutions of ethanol in order to remove the toxic organic solvent “xylene” and rehydrate the tissue. The objective of this study was first to develop a method to deparaffinize FFPE blocks that excludes the use of toxic solvent “xylene”. Second minimize the time required to perform the extraction. Here we describe a method where: • The entire paraffin embedded blocks are deparaffinized and rehydrated using only hot distilled water as a substitute for both xylene and ethanol • The entire procedure takes about 15 min • Deparaffinized blocks are immediately homogenized in lysis buffer, and the obtained lysate analyzed by Western blot. With this new modified technique, we were able to successfully detect actin and AKT proteins in lysates from blocks embedded in paraffin for up to 9 years.